A critical EAP perspective on “Glory to Hong Kong”: Language, identity, and resistance - Wong, Ka Hang (Universitas Ahmad Dahlan, 2025)
This paper examines Hong Kong’s protest anthem “Glory to Hong Kong” as a site of linguistic and ideological resistance. It adopts a three-pronged approach: first, it uses Critical Discourse Analysis (CDA) to uncover how the lyrics construct themes of resistance, perseverance, struggle, and liberation; second, it situates this analysis within political discourse constructed by leading politicians from the People’s Republic of China and the United Kingdom; and third, it explores the pedagogical potential of applying a Critical English for Academic Purposes (CEAP) framework to the anthem. The paper argues that analysing protest discourse in this way offers possibilities for English language classrooms, particularly for exiled learners and migrant communities, equipping them to critically engage with language, power, and identity. By linking textual analysis to classroom practice, it positions the anthem not only as a cultural artifact but also as a resource with the potential to empower learners to interrogate dominant narratives. This study is particularly timely in the wake of China’s imposition of the National Security Law in Hong Kong and the global repression of exiled Hongkongers.